Ottoman wars, 1700-1870 - Aksan, Virginia H., author.
1 online resource.
Keywords: “Originally conceived as a military history, this second edition completes the story of the Middle Eastern populations that underwent significant transformation in the nineteenth century, finally imploding in communal violence, paramilitary activity, and genocide after the Berlin Treaty of 1878. Written by a foremost scholar of the Ottoman Empire and featuring illustrations that have not been seen in print before, this second edition will be essential reading for both students and scholars of the Ottoman Empire, Ottoman society, military and political history, and Ottoman-European relations“--